Strategies for the follow-up of gravitational wave transients with the Cherenkov Telescope Array. Issue 1 (6th March 2018) - Bartos, I; Di Girolamo, T; Gair, J R; Hendry, M; Heng, I S; Humensky, T B; Márka, S; Márka, Z; Messenger, C; Mukherjee, R; Nieto, D; O'Brien, P; et al.
Abstract: The observation of the electromagnetic counterpart of gravitational-wave (GW) transient GW170817 demonstrated the potential in extracting astrophysical information from multimessenger discoveries. The forthcoming deployment of the first telescopes of the Cherenkov Telescope Array (CTA) observatory will coincide with Advanced LIGO/Virgo's next observing run, O3, enabling the monitoring of gamma-ray emission at E > 20 GeV, and thus particle acceleration, from GW sources. CTA will not be greatly limited by the precision of GW localization as it will be capable of rapidly covering the GW error region with sufficient sensitivity. We examine the current status of GW searches and their follow-up effort, as well as the status of CTA, in order to identify some of the general strategies that will enhance CTA's contribution to multimessenger discoveries.